2006
DOI: 10.1177/1087054705284241
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Chinese Version of the Conners’ Parent and Teacher Rating Scales-Revised: Short Form

Abstract: Our findings suggest that the CPRS-R:S-C and CTRS-R:S-C are reliable and valid instruments for measuring inattention and hyperactivity in both clinical and community settings in the Chinese population in Taipei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 32 publications
5
59
1
6
Order By: Relevance
“…Overall, the rates of comorbid conditions of particular behavioral problem pairs in the present study ranged from 0.9% to 4.0%, lower than those reported in the USA (10.5-30.2% in children aged [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. 14 This discrepancy can be explained by different definitions of comorbidity and the age range of the participants.…”
Section: Comorbid Patterns Of Behavioral Problemscontrasting
confidence: 88%
See 2 more Smart Citations
“…Overall, the rates of comorbid conditions of particular behavioral problem pairs in the present study ranged from 0.9% to 4.0%, lower than those reported in the USA (10.5-30.2% in children aged [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. 14 This discrepancy can be explained by different definitions of comorbidity and the age range of the participants.…”
Section: Comorbid Patterns Of Behavioral Problemscontrasting
confidence: 88%
“…3,23 Moreover, the present findings also support the notion that inattention/hyperactivity and thought problems are more prevalent in boys than girls. 18,24 Despite the consistent findings across studies, little has been known about the underlying mechanism of the gender differences in childhood behavioral problems.…”
Section: Gender Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, these two subscales of both parent and teacher reports were used to classify children into four discrete groups. A prior psychometric study has demonstrated that the Chinese version of both the CPRS-R: S and CTRS-R: S are reliable and valid and that they clearly distinguish clinical children with ADHD from those without, with satisfactory sensitivity and specificity [33]. Similar factor structures as those of the English version have been obtained for the Chinese CPRS-R: S and CTRS-R: S [33].…”
Section: Adhd and Odd Symptomsmentioning
confidence: 70%
“…(14) The short form of the CPRS, which consists of 27 items concerning a variety of childhood behavioural problems, (15) was used in this study. Mothers were asked to rate each item according to their child's behaviour over the last month on a …”
Section: Resultsmentioning
confidence: 99%